Role of Translingual Pedagogies for Invoking Creative and Critical Skills: A Case Study - Hajra Bibi (University of Chitral Journal of Linguistics and Literature, 2023)
A quantitative and descriptive study is conducted to see the attitude of Pakistani ESL teachers towards the use of ‘Translingual pedagogy’. Survey Method is used to collect data via google forms. The sample of the study consists of 170 English teachers teaching to undergraduate students in Pakistani universities and affiliated colleges. The tool contained three sections. The first section gathered information about the demographics of the participants; the second focused on the class practices of the ESL teachers and the third section had questions about the use of Urdu language in ESL classrooms. The Likert scale is used to provide different options to the participants. In order to check the reliability of the tool, Cronbach Alpha test is used. For validity check, research tool is evaluated and approved by 5 university Professors. Findings show that Pakistani ESL teachers are successfully using this pedagogy and claim that this teaching technique helps in developing the understanding, cognitive, creative and critical abilities of the ESL learners. In addition, translanguaging motivates ESL learners to actively participate in classroom activities. It has a positive impact on the learning abilities of the ESL undergraduate students. Keywords: Translingual pedagogy, ESL, effectiveness, creative and critical skills